2010
DOI: 10.1159/000320552
|View full text |Cite
|
Sign up to set email alerts
|

Long-term High-fat-diet Feeding Impairs Mitochondrial Biogenesis in Liver of Male and Female Rats

Abstract: Background/Aims: Mitochondrial biogenesis includes both mitochondrial proliferation and differentiation and its regulation under different physiological conditions is not clear. Given the sexual dimorphism previously found in mitochondrial function, the aim of this study was to investigate the gender-dependent effect of chronic high-fat-diet (HFD) feeding on rat liver mitochondrial function and biogenesis. Methods: Ten-week old male and female rats were fed a HFD (26% fat) or a control diet (2.9% fat) for 26 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 67 publications
6
31
3
Order By: Relevance
“…Sex differences have been previously described in mitochondrial biogenesis of skeletal muscle [19] and of other tissues, such as liver [20,21] brain [22], heart [23] and brown adipose tissue [24,25]. Moreover, we have also reported a higher skeletal muscle antioxidant capacity and a better insulin sensitivity profile in response to high fat diet (HFD) feeding in female rats compared to males [26].…”
Section: Introductionmentioning
confidence: 54%
“…Sex differences have been previously described in mitochondrial biogenesis of skeletal muscle [19] and of other tissues, such as liver [20,21] brain [22], heart [23] and brown adipose tissue [24,25]. Moreover, we have also reported a higher skeletal muscle antioxidant capacity and a better insulin sensitivity profile in response to high fat diet (HFD) feeding in female rats compared to males [26].…”
Section: Introductionmentioning
confidence: 54%
“…The structural and functional differences of mitochondria between sexes per se may play a role. Male rats show lower mitochondrial oxidative capacity [44] and higher oxidative stress [45] compared to females, which render males more susceptible to diseases associated with mitochondria dysfunction [46]. Early studies have shown that glucocorticoid stimulates mitochondrial RNA synthesis [47], [48], thereby contributes to the regulation of mtDNA encoded OXPHOS gene expression and protein synthesis in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, E2 has a beneficial role in some tissues such as: heart, brain, muscle, brown adipose tissue, and liver [32][33][34], where this hormone increases mitochondrial function. This effect agrees with studies that shown more functional mitochondria in female rats and these findings have been associated with a lower oxidative stress [35,36].…”
Section: Discussionmentioning
confidence: 99%